Rainfall Data as an Indicator of Climate Change (Case Study: Kuta District, Badung Regency) - Yasa, I Putu Bagus Reka Sugita; Pujianiki, Ni Nyoman; Pariartha, I Putu Gustave Suryantara (Sainteks: Jurnal Sain dan Teknik, 2025)
Climate change is a global issue that has a clear impact on rainfall patterns, especially in coastal areas. This study examines rainfall changes in Kuta District, Badung Regency, using CHIRPS satellite data from 1981 to 2024. The validity of CHIRPS data was confirmed by comparing it with data from the Ngurah Rai meteorological station (1 station; 1981–2020 period; monthly scale) by matching the CHIRPS grid to the station location. The validation showed a high level of accuracy (r = 0.934; R² = 0.878), thus proving the reliability of CHIRPS as a data source. Trend analysis using the Mann-Kendall test, along with Sen's slope calculation (+7.92 mm/year; 95% CI), showed a statistically significant increase (p < 0.05). Furthermore, trend testing on the extreme rainfall intensity index (R50mm, RX1day) revealed an increase in the frequency of heavy rainfall after 2019, which was confirmed by indications of abrupt changes based on the Pettitt test. The results of this study align with scientific publications and climate change projections in tropical regions. These findings emphasize the importance of monitoring using remote sensing technology in areas with limited rain gauge stations. These findings imply the need to formulate adaptation strategies related to hydrometeorology and improved water resource management.